1989
DOI: 10.1111/j.1532-5415.1989.tb02640.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous‐Delayed Hypersensitivity in Nursing Home and Geriatric Clinic Patients

Abstract: Cutaneous-delayed hypersensitivity was studied by one and two-step Mantoux-type skin tests to four standard antigens in 33 elderly nursing home residents, 34 geriatric clinic patients, and 20 healthy young adult controls. Demographic and anthropometric data were collected to determine the effects of nutrition and other variables on cutaneous-delayed hypersensitivity. Anergy (a lack of response greater than 5 mm of induration when read at 48 hours) to any of the four antigens occurred in 34% of nursing home res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Diminished immune responses among elderly individuals include demonstration of decreased delayed hypersensitivity, lower antibody titer in response to vaccination [11,12], low rates of seroconversion following vaccination, increased risk of death from influenza or pneumonia [13], and more frequent reemergence of tuberculosis [14] relative to younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished immune responses among elderly individuals include demonstration of decreased delayed hypersensitivity, lower antibody titer in response to vaccination [11,12], low rates of seroconversion following vaccination, increased risk of death from influenza or pneumonia [13], and more frequent reemergence of tuberculosis [14] relative to younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of false negative responses was considered. It has been shown that age (both the very young and the very old) can be responsible for false negative TST reactivity [27], [28] but other causes of false negative results include immunosuppression [29], overwhelming TB infection [30], other viral [29], [31] or bacterial infections [32] and recent viral vaccinations [33], [34]. In our study the TST and blood collection were only performed on healthy children and HIV rates in infants are very low in The Gambia suggesting the lack of TST reactivity observed in some individuals was not due to false negative responses.…”
Section: Discussionmentioning
confidence: 99%
“…T cells in DTH response and age-associated defects in T-cells, it is expected that aging would decrease DTH response. Indeed, the elderly individuals exhibit impaired DTH response (the number of positive responses and/or diameter of induration) [42][43], which are correlated with their greater morbidity and mortality [44][45][46].…”
Section: Source Of Immune Cellsmentioning
confidence: 99%